LncRNA SLNCR phenocopies the E2F1 DNA binding site to promote melanoma progression - Kushani Shah; Eleni Anastasakou; Leinal Sejour; Yufei Wang; Leon Wert-Lamas; Christopher Rauchet; Sabine Studer; Simon Goller; Robert J. Distel; Wayne Marasco; Lalith Perera; Ioannis S. Vlachos; et al. (Cell Reports)
Summary: The long non-coding RNA SLNCR and the transcription factor E2F1 are known melanoma oncogenes. We show that SLNCR binds to E2F1 to promote the proliferation, invasion, and migration of melanoma cells from the bloodstream into the lungs. Blocking SLNCR-E2F1 complex formation without reducing the levels of either SLNCR or E2F1 prevents lung extravasation in mice. A 60-nt fragment of SLNCR contains two RNA analogs of the E2F1 DNA binding site (BS) in opposite orientations and can form a hairpin RNA that phenocopies the E2F1 DNA BS. Molecular dynamics (MD) simulations and biochemical experiments indicate that this fragment of SLNCR binds to the E2F1 DNA-binding domain more effectively than the E2F1 DNA BS. MD simulations predict higher affinity for DNA-E2F1 complex formation but faster kinetics and a greater number of RNA-amino acid contacts for the RNA-E2F1 complex, suggesting that RNA binding to E2F1 is more kinetically favorable.